2022
DOI: 10.3389/fped.2022.899193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breast Milk Oral Care on Mechanically Ventilated Preterm Infants: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: BackgroundThe benefits of breast milk oral care in mechanically ventilated preterm infants remain controversial. This study aimed to systematically review the evidence on the benefits of breast milk oral care in mechanically ventilated preterm infants.MethodsThe randomized controlled trials of breast milk oral care for mechanically ventilated preterm infants were searched in EMBASE, PubMed, Cochrane Library, Web of Science, WANFANG Date and China National Knowledge Infrastructure databases. The retrieval langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
1
3
0
2
Order By: Relevance
“…In the present study, we foundan association between OCI and a smaller median of length of hospitalization in the group of preterm newborns ≥ 28 gestational age weeks. This finding is in line with the result of the last published meta-analyses, 11,20,21 which assessed only controlled clinical trials 5,6,8,12,14,15,[17][18][19] and reported lower length of hospitalization in the group of preterm newborns <34 and ≥32 weeks of gestational age in OCI, respectively. 11,20,21 However, the result that we found differs from other meta-analysis 22 that had favorable outcomes for the control group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, we foundan association between OCI and a smaller median of length of hospitalization in the group of preterm newborns ≥ 28 gestational age weeks. This finding is in line with the result of the last published meta-analyses, 11,20,21 which assessed only controlled clinical trials 5,6,8,12,14,15,[17][18][19] and reported lower length of hospitalization in the group of preterm newborns <34 and ≥32 weeks of gestational age in OCI, respectively. 11,20,21 However, the result that we found differs from other meta-analysis 22 that had favorable outcomes for the control group.…”
Section: Discussionsupporting
confidence: 87%
“…6,8,9,12,[16][17][18][19] Meta-analysis researches, published between 2020 and 2023, found out that hospitalization was significantly reduced in the treatment group. 11,20,21 however, previous studies have demonstrated favorable outcome for the control group 22 or did not observe significant difference. 2,3,10,13 The divergence between results reinforce the need for further investigations regarding the effect of OCI in the length of hospital stay of preterm newborns, a relevant subject for public health.…”
Section: Introductionmentioning
confidence: 88%
“…They found that the fresh HM group had a shorter duration of mechanical ventilation than the control group. Finally, a 2022 metaanalysis shows that not only HM feeding, but also oral care of preterm infants with mother's milk shortens the mechanical ventilation time [17]. It is remarkable that despite large differences in the way the various research groups provide HM to infants in neonatal care, HM is associated in all cases with a reduction of respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the fresh HM group had a shorter duration of mechanical ventilation than did the control group. Finally, a 2022 meta-analysis showed that not only HM feeding but also oral care of preterm infants with mother’s milk shortens the mechanical ventilation time [ 24 ]. It is remarkable that despite large differences in the way various research groups provide HM to infants in neonatal care, HM is associated with reduced respiratory support in all cases.…”
Section: Discussionmentioning
confidence: 99%